Studies On The Chemical Composition And Biological Activities Of Essential Oils Of Goniothalamus Spp. - Irna Syairina, Sahari (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Essential oil of eight (iouior/tal(ll!l!n spp. haq: ])('(..'11 ootractoo by hydrodi~lll1alion and their chemkal oompoSlti()n W"''fC deh.'Jmim:J by gas cbmmatogruphyltlame IOnil.lltion dc1C'Ctor lGC/FID) tl"Chniqut' and biological a ...1ivity on brine shrimp•.4.nemiO sal/,UI and tennit~. Naslllilemlf!S sp. II en: evaluated. The per<''<.l1tage yield of~~cntial OIl for all samples studied ranged bdwe-Cll 0.1 8% to 5.00% (I'olume/dry weight). Thc lean:,; oil ofG, rapis gal'e thc highest )'idd of essential oil (5.00%). while the stC1n bark oil of C. I<"ljQ(lii gaves lhe lowest YIeld (O.IK%l. The major compound in thc leaves oil of G malaymms was 2-dod.:ccnal 117.90"/,) and in the k,l\"1tS oil of G. am/er.mnii was mcthyllaur.l[e (18.il %). The leal'cs oil of G. lapis was rich in with ~ bourbonene (14.80'%). while dch}'drocarv<''Q1 (42.35%1 \\"(-re rich in the: hark oil. (E)-2-nnnenal (57.76%) in the SK,n bark nil ami 3-~'Ud..:'Smol (29.82%) 111 the root nil. The leave; nils of C. 1I,'al"ivde.$ was rich in bulsll1(\1 (10.92'%) and butylmdhoxYPYTll7inlo' ,38.920/0) from the stem bark oil. \1 hCfea~ lE}-2..JoJcccn-l-ol II 1.54%) was mnst abundance in the rool OIl. Valmecnc (14.31 %) \\as ilhundante 111 the leavcs oil of G, ...vodii, mCl hykthylpyra.,dne (I S.OR%) was the majt)r compuund in it~ ~tem bark oil and butyl dccanoatc (10.65%) was thl: major compound in its rOOt Otl. 2-dool"Cellal (11.05%) was the major constit'uem in tlte leal'CS ml of C. /aseielll'lIInlS. cadina-1.4-dill1-3-oll42.90"-io) in the: bark oi1. a-bisabnlol (36.49% ) in the Stem bark oil. while: (Z)~6JOOcccn-y-Ial.1.onc (\9.95%) was rich in the rool oil. The 1('31'C::; nil of (j frl1l{"c/mIlS was illso rich wilh 2-dodccell31 (12J6%), IIoh!le: (-)·eubt:nol (25.97%) was the major cunstitue!1t in bark OIl. cadinn· 1.4.dien·3·oll44.90%) was the major compound in S1em hMk oil and {E)-a-bergamotcne (23 .01 %) was the ma)\1r W111p!.)und in TUot oil. G. lapisoit/e.~ was rich with methyl t:pijasmonatc 29.011%) in its leavcs oil. g<'T3nyl I alcratc (9.61 'lie) in its bark oil. and eadina· [.4·dien·3-o1 (30.89"/0) m liS Stdl1 bark uil. a5 well as p.eudcsmol l36.66%) as major l~)11~tilUC'nt in its root oil. All th.' ...'S~cntial nil showed ICI()% mortality of the hrine ~hritnp. A, ID.lilla ~t the ~onct:lllration of Illorc than 100 ppm, whert: the kaves OIl of C. IImriQCh~$ showl.'d strongc:st acti\'ity (1.(''<1 valuc < 10 :'1'111). Tt.'fmiticidal activity Icst showl.'d that all the essential 011studied gave: l000A. monalily al conct'11tration tlf more than \ 'Yo. ~C"i.'Pt flIT !he leaves oil of G. It"Q()(/ii. The leaves oils of (;. rapisoides exhit.ik'd ;;trongcst netfl,;ty with LC<.(I value less th~n 0,1% igain~t NaS l/ lilerl!les sp. td"lllite. while the Icaw:s oil ofG, lI'ood/i showed th~ weakest activity with Le .., value of 1.00%.